Mooring forces in a floating point-absorbing WEC system – a comparison between full-scale measurements and numerical simulations. (30th December 2020) - Ringsberg, Jonas W.; Yang, Shun-Han; Lang, Xiao; Johnson, Erland; Kamf, Jonas
ABSTRACT: The study presents an investigation of Waves4Power's WaveEL 3.0 wave energy converter (WEC). It was used as a reference for full-scale measurements of the mooring forces and buoy motions in a measurement campaign 2017 at an installation location off the coast of Runde in Norway. A numerical simulation model of the installation was developed in the DNV GL software SESAM. Unfortunately, the sea state conditions were not measured during the measurement campaign. Hence, a methodology was developed that used the recorded motion data to compute the sea state conditions at the test site. The simulated WEC motions based on the computed sea states agreed very well with the measured WEC motions. The measured and simulated mooring forces were compared under various environmental conditions. 3-hour sea state realizations are typically preferred in numerical simulations. However, influences from the tide at the test site showed that sea states were normally stationary for only 1–2 h. The measured and simulated average mooring forces agreed very well during 1-hour periods, whereas the simulations overestimated the mooring forces in 3-hour periods because of the tide.